Response of Launch Pad Structures to Random Acoustic Excitation - Ravi N. Margasahayam; Raoul E. Caimi (Shock and Vibration)
The design of launch pad structures, particularly those having a large area-to-mass ratio, is governed by launch-induced acoustics, a relatively short transient with random pressure amplitudes having a non-Gaussian distribution. The factors influencing the acoustic excitation and resulting structural responses are numerous and cannot be predicted precisely. Two solutions (probabilistic and deterministic) for the random vibration problem are presented in this article from the standpoint of their applicability to predict the response of ground structures exposed to rocket noise. Deficiencies of the probabilistic method, especially to predict response in the low-frequency range of launch transients (below 20 Hz), prompted the development of the deterministic analysis. The relationship between the two solutions is clarified for future implementation in a finite element method (FEM) code.